Analysis of the Quality Assurance Effect of Sino-Foreign Cooperative Education from the Perspective of Students: A Case Study in Jiangsu Province, China - Yang, Lili; Chen, Rui; Yao, Dumevi Andrews; Zhang, Ping (Journal of Teaching and Learning, 2026)
Sino-foreign cooperative education (SFCE) refers to the education offered by Sino-foreign cooperative education institutions. Students can gain international educational experience without leaving China. Foreign parties mainly provide teachers, researchers, courses, and resources. From students' perspectives, SFCE has a comprehensive quality-assurance system, strong teacher support, sufficient and effective resources, and efficient management. However, there are some problems, such as students' unclear understanding of the social role of quality assurance, a lack of evidence of process-oriented management in quality assurance content, and weak improvement in scientific-research ability, as reflected in students' learning outcomes. The authors surveyed the quality-assurance effect of SFCE in Jiangsu Province, China, with 587 questionnaires recovered and 546 valid responses. Through the analysis, it was found that the quality-assurance effect of SFCE was affected by curriculum, teacher support, resource and management efficiency, multiple evaluations, and other factors. To further strengthen quality assurance, it is necessary to optimize this system and popularize it, supplement process-management links, highlight social-value guidance, and improve the training system for scientific-research ability by addressing the gap in high-level ability development.